WORKING FROM HOME POLICY FOR INDONESIAN CIVIL SERVANTS DURING CORONAVIRUS DISEASE PANDEMIC - Rochmat Ali Syaefudin (Spirit Publik: Jurnal Administrasi Publik, 2020)
World Health Organization (WHO) has declared Coronavirus disease (COVID-19) as global pandemic. According to 2019 data from the National Civil Service Agency (BKN), Indonesia has more than 4.28 million civil servants across the country. President Joko Widodo has urged everyone to stay at home, (including civil servants)  and work from home. Working from home for Indonesian civil servants were new practice. None Art or Government Regulations regulates work from home policy before. Work from home policy implemented during COVID-19 pandemic in a bid to crub virus spreadness. Technology and qualified civil servants need to maintain public services from home. Regulations and Standart Operational Procedures (SOP) of work from home policy need to ensuring public interests and services not interrupted during pandemic period.